PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VB SD NEGERI 62 PEKANBARU - Rina, Rina; Marhadi, Hendri; alexander, Jessi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to improve grade V student’s maths learningachievement at SDN 62 Pekanbaru academic year 2014/ 2015 through “ Application of the model direct learning”. Setting of the problem is “ is the application of the model direct learning can improve grade V student’s maths learning achievement at SDN 62 Pekanbaru”. This research was conducted in February. The number of students are 32 students which contain of 18 boys and 14 girls. This research is classroom action research which contains of three cycles. Each cycles consist of 2 meeting. Parameter of the research is involved students learning achievement after the action in each cycles (daily test I, II,). Instrument of the research contains of learning tools (syllabus, RPP, LKS, LLL, learning result paper sheet). Observation of student and teacher activity sheet. Data of the research will analyze descriptively. Research data show that learning achievement has increased.Where prior to the application of the model direct learning as much as any 12 students (37,5%)scored daily test is above or equal to the minimum completeness criteria (KKM). It was improved to 65% after using the application of the model direct learning in first cycle. In the second cycle increased 90%. Activities of the student during the learning process (I, II cycles) is can be categorized very well by an average 87,5%. From the explanation above shows that application of the model direct learning can be improving grade V students maths learning achievement at SDN 62 Pekanbaru.Keyword :the model direct learning, maths achievement